Best parameters for sexual dimorphism in the facial thickness tissue with ultrasonic assessment - Iván Claudio Suazo Galdames; Guillermo Enrique Salgado Alarcón; Daniela Alejandra Zavando Matamala (Universidade de Sao Paulo, 2008)
Knowledge of facial tissue thickness is crucial to facial reconstruction procedures in forensic sculpture. The literature still brings some controversy on the validity of data obtained for different population groups. The purpose of this study was to investigate sexual dimorphism in the thickness of the facial tissues. The study sample consisted of 43 volunteers, between 24 and 48 years of age, and of normal body mass. Ultrasound measurements of facial tissue thickness were obtained at 14 median and paramedian landmarks. A T test was used to compare measurements from males and females, with a significance level of at least 0.05. Discriminant function analysis was used to determine the points that showed most distinction between the sexes. Measurements at paramedian landmarks were greater in males, while those at median landmarks were greater in female subjects, except for Down's A and B points. We conclude that sexual dimorphism in facial thickness justifies the pre-assignment of sex in reconstruction procedures in forensic sculpture